Transmission of Grapevine Red Blotch Virus by Spissistilus festinus [Say, 1830] (Hemiptera: Membracidae) between Free-Living Vines and Vitis vinifera ‘Cabernet Franc’ - Hoyle, Victoria; Flasco, Madison T.; Choi, Jiyeong; Cieniewicz, Elizabeth J.; McLane, Heather; Perry, Keith; Dangl, Gerald; Rwahnih, Maher Al; Heck, Michelle; Loeb, Greg; Fuchs, Marc F. (Viruses, 2022)
Grapevine red blotch disease emerged within the past decade, disrupting North American vine stock production and vineyard profitability. Our understanding of how grapevine red blotch virus (GRBV), the causal agent of the disease, interacts with its Vitis hosts and insect vector, Spissistilus festinus, is limited. Here, we studied the capabilities of S. festinus to transmit GRBV from and to free-living vines, identified as first-generation hybrids of V. californica and V. vinifera ‘Sauvignon blanc’ (Vcal hybrids), and to and from V. vinifera ‘Cabernet franc’ (Vvin Cf) vines. The transmission rate of GRBV was high from infected Vcal hybrid vines to healthy Vcal hybrid vines (77%, 10 of 13) and from infected Vvin Cf vines to healthy Vcal hybrid vines (100%, 3 of 3). In contrast, the transmission rate of GRBV was low from infected Vcal hybrid vines to healthy Vvin Cf vines (15%, 2 of 13), and from infected Vvin Cf vines to healthy Vvin Cf vines (19%, 5 of 27). No association was found between transmission rates and GRBV titer in donor vines used in transmission assays, but the virus titer was higher in the recipient leaves of Vcal hybrid vines compared with recipient leaves of Vvin Cf vines. The transmission of GRBV from infected Vcal hybrid vines was also determined to be trans-stadial. Altogether, our findings revealed that free-living vines can be a source for the GRBV inoculum that is transmissible by S. festinus to other free-living vines and a wine grape cultivar, illustrating the interconnected roles of the two virus hosts in riparian areas and commercial vineyards, respectively, for virus spread. These new insights into red blotch disease epidemiology will inform the implementation of disease management strategies.